The role of the audiologist–phoniatrician in performing the dynamic endoscopic study of swallowing. Position statement of the Italian study group on dysphagia (GISD)*. (2nd October 2018) - Farneti, Daniele; Schindler, Antonio; Fattori, Bruno; Ruoppolo, Giovanni; Simonelli, Marilia; Coscarelli, Salvatore; Travalca Cupillo, Beatrice; Spadola Bisetti, Massimo; Nacci, Andrea; Genovese, Elisabetta; Barillari, Umberto; Schindler, Oskar
Abstract: This paper expresses the views of a group of experts within the Italian Study Group on Dysphagia (GISD) concerning the role of the Audiologist–Phoniatrician in performing the dynamic endoscopic study of swallowing.